Effectiveness Of Medication Reviews In Identification And Management Of Medication Related Problems By Clinical Pharmacist: Pharmaceutical Science-Pharmacy practice for good health promotion - Sushanta Kumar Das; G. Jayanthi; Modala Shiva Krishna; K. Pheoba Lydia Rani; Gudapu Priyanka (International Journal of Life Science and Pharma Research, 2022)
Medication related problems (MRPs) are any preventable events that lead to inappropriate medication use or patient harm. Clinical pharmacist plays a key role in various clinical activities of hospital and contributes to improve the quality of medication use and patient safety with an aim to provide better patient outcome. Hence our aim in this study is to identify, classify and develop management strategy of various MRPs in a tertiary care teaching hospital and report them to concerned doctors to modify the drug therapy accordingly. Out of total collected cases; prescribing errors (21%) and adverse drug reaction (ADR) (35%) were most common, followed by drug duplication (11%), improper drug selection (8%), untreated indication (7%), double dosing (6%), wrong dose (5%) were frequently repeated drug related issues. Other MRPs were inappropriate dose, omission error, drug without indication and drug insufficiency with very minimal appearance which also satisfy the PCNE categorization of drug related problems. We found that Anticonvulsants and Antibiotics were frequently identified prescription medicine to develop MRPs.. Cerebrovascular accidents and Epilepsy were mostly involved in disease where MRPs were seen frequently. Standard management guidelines were also described to the doctors for individual MRP cases. Certain MRPs were frequently appearing and clinical pharmacists should be alert enough to address them with proper management strategy. Our study highlights the significant role of clinical pharmacist’s intervention in identification of MRPs, which generally remain unidentified unless harm occurs. This study also shows a new avenue of drug therapy optimization by providing proper medication information to overcome identified MRP issues to enhance patient safety and care. Our role was highly accepted and appreciated by various doctors.